Self-healing alginate–gelatin biohydrogels based on dynamic covalent chemistry: elucidation of key parameters. (29th July 2016) - Pettignano, Asja; Häring, Marleen; Bernardi, Luca; Tanchoux, Nathalie; Quignard, Françoise; Díaz Díaz, David
Abstract : Key parameters that govern the self-healing character of alginate–gelatin biohydrogels based on dynamic covalent chemistry have been elucidated. Abstract : In this work, gelatin was crosslinked with oxidized alginate in the presence of borax yielding a hybrid biohydrogel system with the ability to self-repair upon mechanical damage. A judicious balance between concentration, stoichiometric ratio of the two biopolymers and gelatin source was found necessary to achieve optimal self-healing properties of these biohydrogels. The pH was found to have a major influence on the reconstruction of the damaged hydrogel interface, confirming that the dynamic Schiff base linkages between the amine groups of gelatin and the aldehyde groups of oxidized alginate play a fundamental role on the healing process of the hybrid gels.